Cyprus building energy performance methodology: A comparison of the calculated and measured energy consumption results - Panayiotou, Gregoris; Maxoulis, Christos N.; Kalogirou, Soteris A.; Florides, Georgios A.; Papadopoulos, A. M.; Neophytou, M.; Fokaides, P. A.; Georgiou, G.S.; Symeou, A.; Hadjinikolaou, N.; Georgakis, G. (My University, 2010)
In order to fulfil article 4 of the 2002/91/EC Directive (EPBD) a national methodology for the energy performance of buildings was drafted and approved by the Government of Cyprus in 2009. This methodology is in line with the European standards prepared to facilitate EPBD implementation and follows the asset rating approach that is, it represents the intrinsic annual energy use of a building under standardised conditions. CEN standards leave an option, quite suitable for existing and complex buildings, for operational rating, which is an energy rating based on measured amounts of delivered and exported energy. The calculated and measured rating exhibit advantages and disadvantages and as expected the results of the two approaches vary, since the measured rating approach takes into account the effect of user behaviour, the actual weather conditions and the realized (actual) thermal comfort conditions inside the building. This paper presents the Cyprus legal framework for adopting the EPBD and exhibits the Cyprus methodology for the energy performance of buildings. Moreover the advantages and disadvantages of the asset and operational rating approaches are discussed and a comparison of the results of these two approaches for a selected number of dwellings is presented. One of these cases is also examined with respect to the climatic conditions, by changing the climatic zone in which the building is erected. The latter reveals the effect of climate on the calculated energy requirements of the building for both heating and cooling.
Keywords: 2002/91/EC directive (EPBD); Asset rating; Energy rating; Implementation of EPBD; Operational rating national energy performance methodology